Effect of Area Development on the Stability of Cut Slopes. (2015) - Sutejo, Yulindasari; Gofar, Nurly
Abstract: Many natural slopes were subjected to change in geometry in order to make room for construction of infrastructures. This paper presents stability analysis of a natural slope subjected to cutting to make room for the development of factories in an industrial site. The analysis was performed for the most critical slope section and analysis was made in comparison to the case presented in literature. Data required for slope stability analysis were retrieved from relevant project report. The result shows that the stability of the slope decreases due to slope excavation and stabilization should be done in order to limit further reduction of shear strength due to yielding of soil mass. Analysis using circular failure surface such as Simplified Bishop is simple and is usually suitable for analysis of existing slope where there is no indication of incipient failure. However, pre-defined failure surface in Morgensten Price method is more useful if failure surface could be predicted based on slope assessment or when rectification work has been applied.